Unpacking the Lived Experience of High-Income Female Earners in Romantic Relationships - Ntshalintshali, Silindile Noxolo (University of the Witwatersrand, Johannesburg, 2024)
This study explores the complex interconnection between financial power and traditional gender roles faced by high-income women in South Africa. It emphasises the need for nuanced approaches to address internalised beliefs and advocate for societal change. The research highlights the interplay of financial factors, familial dynamics, and cultural norms on relationships. The research aims to explore the experiences of economically empowered women and the interplay between their financial power and traditional gender roles as well as understand the ramifications of gender ideologies on dual-income heterosexual relationships in South Africa. Qualitative research methods were used to capture diverse narratives and perspectives. Women in the study expressed a desire for their partners to have better financial positions, indicating a preference for conventional gender roles. Despite efforts to empower women economically, societal attitudes towards high-income earning women are still shaped by internalised beliefs about gender roles.
A research report submitted in fulfillment of the requirements for the Master of Arts Social and Psychological Research, In the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Financial power; gender equality; gender roles; women empowerment; SDG-5: Gender equality; SDG-8: Decent work and economic growth